Analisa Pengaruh Variasi Suhu Plastik Terhadap Cacat Warpage Dari Produk INjection Molding berbahan PolyProphylene (PP) - Zulianto, Dwi, Bambang Waluyo F.,ST., MT, Ir Pramuko Ilmu P, MT (2015)
Plastic is the material began to dominate replace metal based materials. This is because plastic is known as a versatile material, is easily formed (formability), lightweight, unbreakable stainless, corrosion resistant, more cheap and many of the advantages of plastic in the injection molding production also has disabled warpage problems, among others. Warpage is defective product forms such irregularities bent or twisted. This caused one of which is the temperature of injection. This study was done to determine the percentage of warpage that occurs due to temperature variations when the injection of plastic material into the mold polyphropylene. With variations in temperature, which is between 138°C, 140 °C, 145 °C, 150 °C, 155 °C and 160 °C. From the analysis of defect measurements found that the specimen results warpage of plastic injection of the material polyphropylene with 138°C temperature, 140 °C, 145 °C, 150 °C is not the discovery of defects that occur warpage. At a temperature of 160 °C is found defective greatest warpage is the smallest amount of warpage 3.10, and the largest 4.90 mm with an area of 26.06 Cm 2 and the smallest (33.17%) and the biggest area of 32.40 Cm 2 (41.24%). Optimal temperature in this study was 145 °C. Keywords: injection molding, solidwork, dial indicators, temperature plastic, warpage.